Description of a second deep-water species in the alpheid shrimp genus Bannereus Bruce, 1988 (Malacostraca: Caridea) - Anker, Arthur; Pachelle, Paulo P.g. (Zootaxa, 2020)
Bannereus chani sp. nov. (Caridea: Alpheidae) is described based on a single female specimen collected off south-eastern Taiwan, at a depth of 301–356 m, being the second only species in the genus Bannereus Bruce, 1988. The ovigerous female holotype of the new species differs from the female holotype of B. anomalus Bruce 1988, the type species of the genus, by a series of important morphological characters, for instance, on the major cheliped and third pereiopod, strongly indicating that they represent two distinct species. The non-type male specimen tentatively identified as B. anomalus by Bruce (1988) may well belong to the new species, since it differs from the holotype of B. anomalus essentially by the same criteria as the female holotype of B. chani sp. nov. In addition, B. anomalus is newly recorded from the New Caledonian side of the Coral Sea.